Towards an effective fiscal stimulus: Evidence from Botswana - Sayed O. M. Timuno; Joel Hinaunye Eita (Cogent Economics & Finance, 2020)
While there is a general agreement on the effectiveness of fiscal stimulus, there is no consensus on which stimulus is better. To address this concern, this paper uses a Dynamic Stochastic General Equilibrium (DSGE) model to propose a fiscal stimulus that Botswana can adopt given the slowing mining productivity. The results suggest that short-run macroeconomic stabilisation can be achieved through a cut in labour taxes. This fiscal stimulus generates larger growth multipliers and contributes relatively more employment compared to a cut in consumption tax and increases in government spending. The findings also revealed that a cut in labour taxes improves trade balance, resulting in a greater accumulation of international reserves and has no Dutch disease effects. These results suggest the need for a labour tax policy reform. These results also offer some policy options for other developing countries, which may face similar fiscal risks in future.
Keywords: C61; E62; H30; 330; Botswana; DSGE; fiscal policy; fiscal stimulus